Aluminum-based heat dissipation plate for energy storage battery and preparation process of aluminum-based heat dissipation plate

By applying a coating of epoxy modified graphene material on the aluminum-based heat dissipation plate, the problem of insufficient infrared radiation heat dissipation performance of the aluminum-based heat dissipation plate is solved, the heat dissipation performance and durability are improved, and more effective heat dissipation is achieved.

CN119216196AActive Publication Date: 2024-12-31DONGGUAN ZWAYN NEW ENERGY CO LTD

Patent Information

Application Number
CN202411306763.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-31
Estimated Expiration
2044-09-19

AI Technical Summary

Technical Problem

The infrared radiation heat dissipation performance of the aluminum-based heat dissipation plate is poor, which limits the heat dissipation of heat and leads to insufficient heat dissipation performance of electronic products.

Method used

The surface of the aluminum-based heat dissipation plate is coated with an epoxy resin coating with epoxy modified graphene material. The activated graphene is treated by plasma to increase the surfactant groups and improve the reaction of silicon oxygen bonds and polyethylene glycol The flexible and hydrophilic properties of the material form a crosslinking network to enhance binding performance.

Benefits of technology

It improves the heat exchange area and heat radiation performance of the aluminum-based heat dissipation plate, accelerates the heat dissipation, enhances the durability of the coating and evaporative heat dissipation performance, solves the problem of thermal expansion rate matching of the aluminum-based heat dissipation plate, and improves the overall heat dissipation performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005049449770000141
    Figure BDA0005049449770000141
Patent Text Reader

Abstract

The invention relates to the technical field of heat dissipation plates, in particular to an aluminum-based heat dissipation plate for an energy storage battery and a preparation technology thereof.In order to improve the heat dissipation performance of the aluminum heat dissipation plate, the surface of the aluminum heat dissipation plate is coated with an epoxy resin coating with an epoxy modified graphene material; according to the preparation method, silicon-oxygen bonds and polyethylene glycol groups are introduced to the surface of graphene, so that the molecular flexibility of a grafted chain segment on the surface of the graphene is improved, and the phenomenon of coating falling caused by mismatching of thermal expansion volumes of an epoxy resin coating and an aluminum substrate is avoided; epoxy modified graphene and epoxy resin are mixed and then co-cured and cross-linked to prepare the heat dissipation coating, in the process, epoxy groups on the surface of the graphene and the epoxy resin jointly participate in cross-linking of a curing agent, so that a cross-linked network is formed, the bonding performance between the graphene and the coating is greatly improved, and the durability of the coating is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of heat sinks, and in particular to an aluminum-based heat sink for an energy storage battery and a preparation process thereof. Background Art

[0002] With the development of modern electronic products, electronic products tend to be miniaturized, and the density per unit area is also increasing. Although this brings superior performance improvement to electronic products, it is accompanied by serious heating. Therefore, electronic products currently have extremely high requirements for heat dissipation. As the final product of the heat dissipation system, the heat sink limits the heat dissipation performance of the heat dissipation system.

[0003] Currently, aluminum-based heat sinks have become the mainstream of heat sinks due to their light weight and good metal thermal conductivity. However, aluminum-based heat sinks have poor infrared radiation heat dissipation performance, which seriously limits the dissipation of heat. Summary of the invention

[0004] The object of the present invention is to provide an aluminum-based heat sink for an energy storage battery and a preparation process thereof, so as to solve the problems raised in the prior art.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A preparation process of an aluminum-based heat sink for an energy storage battery comprises the following steps:

[0007] S1. After polishing the surface of the aluminum substrate to remove the oxide layer, the surface is cleaned with anhydrous ethanol and acetone, dried, and set aside;

[0008] S2. Preparation of heat dissipation coating;

[0009] Mix bisphenol A epoxy resin, epoxy-modified graphene, organic solvent and defoamer, stir and mix for 30-45 minutes, remove bubbles in vacuum, add curing agent, and continue mixing for 2-4 minutes to obtain heat dissipation coating;

[0010] S3. Spray the obtained heat dissipation coating onto the surface of the aluminum substrate, heat it to 85-95°C, and dry it for 8-20 minutes to obtain an aluminum-based heat dissipation plate for energy storage batteries.

[0011] Further, in step S2, the preparation method of the epoxy-modified graphene is:

[0012] S21. placing graphene in a closed chamber, evacuating the chamber and filling it with oxygen until the pressure is 15-50 Pa, subjecting the graphene to plasma treatment, and obtaining activated graphene after the treatment;

[0013] S22. The activated graphene is dispersed in anhydrous ethanol, and after ultrasonic dispersion for 2-4 hours, KH-550 silane coupling agent and deionized water are added thereto, the temperature is raised to 55-65°C, and the reaction is stirred for 4-8 hours. The precipitate is collected by filtration, washed with anhydrous ethanol, and then dried and dispersed again in 1,1,3,3-tetramethyl-1,3-bis[3-(oxiranylmethoxy)propyl]disiloxane, the temperature is raised to 75-85°C, triethanolamine is added, and the ultrasonic oscillation reaction is continued for 1-8 hours. The precipitate is separated by centrifugation, washed with ether, and dried to constant weight to obtain the primary epoxy-modified graphene;

[0014] S23. Disperse polyethylene glycol 200 in DMF, stir evenly, and add it dropwise to a DMF solution containing p-phenylene diisocyanate and dibutyltin dilaurate under nitrogen atmosphere for 1-4 hours. During the addition, the system temperature is controlled to be 34-40°C. After the addition is completed, continue to stir and react for 1-2 hours, add the initial epoxy-modified graphene, continue to react by ultrasonic oscillation for 2-8 hours, centrifuge and precipitate, and vacuum dry to constant weight to obtain hydrophilic modified graphene;

[0015] S24. The hydrophilic modified graphene is dispersed in DMF, ultrasonically dispersed for 1-1.5 hours, mixed with 1,6-hexanediol diglycidyl ether, added with zinc formate, heated to 35-45° C., stirred for reaction for 2-6 hours, and centrifuged to separate the precipitate to obtain epoxy-modified graphene;

[0016] Furthermore, in step S21, during the plasma treatment, the discharge power is 150-300 W, and the treatment time is 5-8 min.

[0017] Furthermore, in step S22, the mass ratio of the activated graphene, KH-550 silane coupling agent, and deionized water is (0.5-1.5): (25-50): (15-25).

[0018] Furthermore, in step S22, the mass ratio of the activated graphene, 1,1,3,3-tetramethyl-1,3-bis[3-(oxiranylmethoxy)propyl]disiloxane, and triethanolamine is (0.5-1.5):50:(0.1-0.9).

[0019] Furthermore, in step S23, the mass ratio of polyethylene glycol 200, p-phenylene diisocyanate, and dibutyltin dilaurate is 10:(6.5-8.1):(0.08-0.12).

[0020] Furthermore, in step S23, the mass ratio of the polyethylene glycol 200 to the primary epoxy-modified graphene is 10:(0.5-1.5).

[0021] Furthermore, in step S24, the mass ratio of hydrophilic modified graphene, 1,6-hexanediol diglycidyl ether, and zinc formate is (0.5-1.5):40:(0.07-0.1).

[0022] Furthermore, in step S2, the heat dissipation coating is composed of 20-30 parts of bisphenol A epoxy resin, 4-8 parts of epoxy-modified graphene, 30-40 parts of organic solvent, 0.5-1 part of defoaming agent, and 3-7 parts of curing agent in parts by weight.

[0023] Furthermore, in step S2, the organic solvent is a mixed solvent of xylene and butanol in a mass ratio of 2:3;

[0024] The defoaming agent is an organosilicon defoaming agent; and the curing agent is dicyandiamide.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] In order to improve the heat dissipation performance of the aluminum heat sink, the present invention applies an epoxy resin coating with epoxy-modified graphene material on its surface; the graphene material has high thermal conductivity, which is conducive to the rapid dispersion of heat, and the graphene surface area is high. Adding it to the coating can effectively increase the surface area of ​​the coating, thereby improving the heat exchange area and heat radiation performance of the coating, and then accelerating the dissipation of heat to the air;

[0027] On this basis, the present invention also performs a modification treatment on the graphene material, activates the graphene surface by plasma treatment, increases its surface active groups, and forms more amino groups on the surface after subsequent reaction with KH-550, and the material of the heat dissipation coating prepared by the present invention is epoxy resin. Compared with the aluminum substrate, the thermal expansion coefficient of epoxy resin is lower, so when facing temperature changes, the coating often falls off due to the mismatch of thermal expansion volume. Therefore, the present invention uses 1,1,3,3-tetramethyl-1,3-bis[3-(oxiranylmethoxy)propyl]disiloxane containing silicon oxygen bonds to react with graphene containing amino groups, thereby realizing the initial epoxidation treatment of graphene, and the introduction of silicon oxygen bonds can effectively increase the molecular flexibility of the grafted chain segments on the surface of the graphene material;

[0028] After that, the present invention also uses polyethylene glycol 200 to react with p-phenylene diisocyanate, and then reacts with epoxy-modified graphene again, thereby continuing to increase the segment length and flexibility of the grafted segment on the surface of the graphene material; at the same time, the polyethylene glycol segment introduced in this process is hydrophilic, which can effectively improve the hydrophilicity of the coating, and is conducive to the flattening of water vapor and water droplets on the surface of the coating, thereby increasing the evaporative heat dissipation performance during heat dissipation; and because the filler used in the present invention is graphene, which is a two-dimensional material, it can effectively block the tiny pores after the epoxy resin is cured, and can effectively avoid the problems such as the decrease in coating durability caused by the erosion of water vapor and salt spray by the polyethylene glycol introduced into the epoxy resin; after the hydrophilic modified graphene is once again epoxidized, the epoxy-modified graphene is mixed with the epoxy resin and co-cured and cross-linked to obtain a heat dissipation coating. In this process, the epoxy group on the surface of the graphene will participate in the cross-linking of the curing agent together with the epoxy resin, thereby forming a cross-linked network, which greatly increases the bonding performance between the graphene and the coating, and effectively increases the durability of the coating. DETAILED DESCRIPTION

[0029] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.

[0030] In the examples and comparative examples of the present application, the diameter of the graphene sheets used is 5-10 μm and the thickness is 3-10 nm; the average particle size of the nano-silicon dioxide used is 30 nm;

[0031] The epoxy resin used is E51 bisphenol A epoxy resin; the organic solvent used is a mixed solvent of xylene and butanol in a mass ratio of 2:3; the defoaming agent used is FLOWNON AO-5 silicone defoaming agent;

[0032] Embodiment 1. A process for preparing an aluminum-based heat sink for an energy storage battery, comprising the following steps:

[0033] S1. After polishing the surface of the aluminum substrate to remove the oxide layer, the surface is cleaned with anhydrous ethanol and acetone, dried, and set aside;

[0034] S2. Preparation of heat dissipation coating;

[0035] S21. By weight, 0.5 parts of graphene were placed in a closed chamber, and after evacuation, oxygen was filled therein to a pressure of 20Pa, and the graphene was subjected to plasma treatment, the plasma discharge power was 150W, the treatment time was 6min, and after the treatment, activated graphene was obtained;

[0036] S22. Disperse 0.5 parts of activated graphene in anhydrous ethanol by weight, ultrasonically disperse for 2-4 hours, add 25 parts of KH-550 silane coupling agent and 15 parts of deionized water, heat to 55 ° C, stir and react for 6 hours, filter and collect the precipitate, wash with anhydrous ethanol, dry and disperse it again in 50 parts of 1,1,3,3-tetramethyl-1,3-bis[3-(oxiranylmethoxy)propyl]disiloxane, heat to 80 ° C, add 0.5 parts of triethanolamine, continue ultrasonic vibration reaction for 6 hours, centrifuge and separate the precipitate, wash the precipitate with ether, and dry to constant weight to obtain the initial epoxy-modified graphene;

[0037] S23. Disperse 10 parts of polyethylene glycol 200 in DMF by weight, stir evenly, and add it dropwise to a DMF solution containing 6.5 parts of p-phenylene diisocyanate and dibutyltin dilaurate under nitrogen atmosphere for 2.5 hours. During the addition, the system temperature is controlled to be 36-38°C. After the addition is completed, continue to stir and react for 1.5 hours, add 0.5 parts of the primary epoxy-modified graphene, continue the ultrasonic oscillation reaction for 5 hours, centrifuge the precipitate, and vacuum dry to constant weight to obtain hydrophilic modified graphene;

[0038] S24. Disperse 0.5 parts of hydrophilic modified graphene in DMF by weight, disperse it by ultrasonic dispersion for 1.5 hours, mix it with 40 parts of 1,6-hexanediol diglycidyl ether, add 0.1 parts of zinc formate, heat it to 40 ° C, stir the reaction for 4 hours, and centrifuge to separate the precipitate to obtain epoxy-modified graphene;

[0039] S25. By weight, 25 parts of bisphenol A epoxy resin, 4 parts of epoxy-modified graphene, 35 parts of organic solvent, 0.8 parts of defoamer were mixed, stirred and mixed for 30 minutes, vacuum defoamed, 4 parts of dicyandiamide curing agent were added, and mixing was continued for 2 minutes to obtain a heat dissipation coating;

[0040] S3. Spray the obtained heat dissipation coating on the surface of the aluminum substrate, heat it to 85-95°C, dry it for 8-20 minutes, and form a heat dissipation coating with a dry film thickness of 20 microns on the surface of the aluminum substrate to obtain an aluminum-based heat dissipation plate for energy storage batteries.

[0041] Embodiment 2. A process for preparing an aluminum-based heat sink for an energy storage battery, comprising the following steps:

[0042] Compared with Example 1, this embodiment increases the amount of epoxy-modified graphene added in step S25;

[0043] S1. After polishing the surface of the aluminum substrate to remove the oxide layer, the surface is cleaned with anhydrous ethanol and acetone, dried, and set aside;

[0044] S2. Preparation of heat dissipation coating;

[0045] S21. By weight, 0.5 parts of graphene were placed in a closed chamber, and after evacuation, oxygen was filled therein to a pressure of 20Pa, and the graphene was subjected to plasma treatment, the plasma discharge power was 150W, the treatment time was 6min, and after the treatment, activated graphene was obtained;

[0046] S22. Disperse 0.5 parts of activated graphene in anhydrous ethanol by weight, ultrasonically disperse for 2-4 hours, add 25 parts of KH-550 silane coupling agent and 15 parts of deionized water, heat to 55 ° C, stir and react for 6 hours, filter and collect the precipitate, wash with anhydrous ethanol, dry and disperse it again in 50 parts of 1,1,3,3-tetramethyl-1,3-bis[3-(oxiranylmethoxy)propyl]disiloxane, heat to 80 ° C, add 0.5 parts of triethanolamine, continue ultrasonic vibration reaction for 6 hours, centrifuge and separate the precipitate, wash the precipitate with ether, and dry to constant weight to obtain the initial epoxy-modified graphene;

[0047] S23. Disperse 10 parts of polyethylene glycol 200 in DMF by weight, stir evenly, and add it dropwise to a DMF solution containing 6.5 parts of p-phenylene diisocyanate and dibutyltin dilaurate under nitrogen atmosphere for 2.5 hours. During the addition, the system temperature is controlled to be 36-38°C. After the addition is completed, continue to stir and react for 1.5 hours, add 0.5 parts of the primary epoxy-modified graphene, continue the ultrasonic oscillation reaction for 5 hours, centrifuge the precipitate, and vacuum dry to constant weight to obtain hydrophilic modified graphene;

[0048] S24. Disperse 0.5 parts of hydrophilic modified graphene in DMF by weight, disperse it by ultrasonic dispersion for 1.5 hours, mix it with 40 parts of 1,6-hexanediol diglycidyl ether, add 0.1 parts of zinc formate, heat it to 40 ° C, stir the reaction for 4 hours, and centrifuge to separate the precipitate to obtain epoxy-modified graphene;

[0049] S25. By weight, 25 parts of bisphenol A epoxy resin, 8 parts of epoxy-modified graphene, 35 parts of organic solvent, 0.8 parts of defoamer were mixed, stirred and mixed for 30 minutes, vacuum defoamed, 4 parts of dicyandiamide curing agent were added, and mixing was continued for 2 minutes to obtain a heat dissipation coating;

[0050] S3. Spray the obtained heat dissipation coating on the surface of the aluminum substrate, heat it to 85-95°C, dry it for 8-20 minutes, and form a heat dissipation coating with a dry film thickness of 20 microns on the surface of the aluminum substrate to obtain an aluminum-based heat dissipation plate for energy storage batteries.

[0051] Embodiment 3. A process for preparing an aluminum-based heat sink for an energy storage battery, comprising the following steps:

[0052] Compared with Example 1, this example increases the amount of p-phenylene diisocyanate added in step S23;

[0053] S1. After polishing the surface of the aluminum substrate to remove the oxide layer, the surface is cleaned with anhydrous ethanol and acetone, dried, and set aside;

[0054] S2. Preparation of heat dissipation coating;

[0055] S21. By weight, 0.5 parts of graphene were placed in a closed chamber, and after evacuation, oxygen was filled therein to a pressure of 20Pa, and the graphene was subjected to plasma treatment, the plasma discharge power was 150W, the treatment time was 6min, and after the treatment, activated graphene was obtained;

[0056] S22. Disperse 0.5 parts of activated graphene in anhydrous ethanol by weight, ultrasonically disperse for 2-4 hours, add 25 parts of KH-550 silane coupling agent and 15 parts of deionized water, heat to 55 ° C, stir and react for 6 hours, filter and collect the precipitate, wash with anhydrous ethanol, dry and disperse it again in 50 parts of 1,1,3,3-tetramethyl-1,3-bis[3-(oxiranylmethoxy)propyl]disiloxane, heat to 80 ° C, add 0.5 parts of triethanolamine, continue ultrasonic vibration reaction for 6 hours, centrifuge and separate the precipitate, wash the precipitate with ether, and dry to constant weight to obtain the initial epoxy-modified graphene;

[0057] S23. Disperse 10 parts of polyethylene glycol 200 in DMF by weight, stir evenly, and add it dropwise to a DMF solution containing 8.1 parts of p-phenylene diisocyanate and dibutyltin dilaurate under nitrogen atmosphere for 2.5 hours. During the addition, the system temperature is controlled to be 36-38°C. After the addition is completed, continue to stir and react for 1.5 hours, add 0.5 parts of the primary epoxy-modified graphene, continue to react by ultrasonic vibration for 5 hours, centrifuge and precipitate, and vacuum dry to constant weight to obtain hydrophilic modified graphene;

[0058] S24. Disperse 0.5 parts of hydrophilic modified graphene in DMF by weight, disperse it by ultrasonic dispersion for 1.5 hours, mix it with 40 parts of 1,6-hexanediol diglycidyl ether, add 0.1 parts of zinc formate, heat it to 40 ° C, stir the reaction for 4 hours, and centrifuge to separate the precipitate to obtain epoxy-modified graphene;

[0059] S25. By weight, 25 parts of bisphenol A epoxy resin, 4 parts of epoxy-modified graphene, 35 parts of organic solvent, 0.8 parts of defoamer were mixed, stirred and mixed for 30 minutes, vacuum defoamed, 4 parts of dicyandiamide curing agent were added, and mixing was continued for 2 minutes to obtain a heat dissipation coating;

[0060] S3. Spray the obtained heat dissipation coating on the surface of the aluminum substrate, heat it to 85-95°C, dry it for 8-20 minutes, and form a heat dissipation coating with a dry film thickness of 20 microns on the surface of the aluminum substrate to obtain an aluminum-based heat dissipation plate for energy storage batteries.

[0061] Embodiment 4. A process for preparing an aluminum-based heat sink for an energy storage battery, comprising the following steps:

[0062] Compared with Example 1, this embodiment increases the plasma treatment discharge power in step S21;

[0063] S1. After polishing the surface of the aluminum substrate to remove the oxide layer, the surface is cleaned with anhydrous ethanol and acetone, dried, and set aside;

[0064] S2. Preparation of heat dissipation coating;

[0065] S21. By weight, 0.5 parts of graphene were placed in a closed chamber, and after evacuation, oxygen was filled therein to a pressure of 20 Pa, and the graphene was subjected to plasma treatment, the plasma discharge power was 300 W, the treatment time was 6 min, and after the treatment, activated graphene was obtained;

[0066] S22. Disperse 0.5 parts of activated graphene in anhydrous ethanol by weight, ultrasonically disperse for 2-4 hours, add 25 parts of KH-550 silane coupling agent and 15 parts of deionized water, heat to 55 ° C, stir and react for 6 hours, filter and collect the precipitate, wash with anhydrous ethanol, dry and disperse it again in 50 parts of 1,1,3,3-tetramethyl-1,3-bis[3-(oxiranylmethoxy)propyl]disiloxane, heat to 80 ° C, add 0.5 parts of triethanolamine, continue ultrasonic vibration reaction for 6 hours, centrifuge and separate the precipitate, wash the precipitate with ether, and dry to constant weight to obtain the initial epoxy-modified graphene;

[0067] S23. Disperse 10 parts of polyethylene glycol 200 in DMF by weight, stir evenly, and add it dropwise to a DMF solution containing 6.5 parts of p-phenylene diisocyanate and dibutyltin dilaurate under nitrogen atmosphere for 2.5 hours. During the addition, the system temperature is controlled to be 36-38°C. After the addition is completed, continue to stir and react for 1.5 hours, add 0.5 parts of the primary epoxy-modified graphene, continue the ultrasonic oscillation reaction for 5 hours, centrifuge the precipitate, and vacuum dry to constant weight to obtain hydrophilic modified graphene;

[0068] S24. Disperse 0.5 parts of hydrophilic modified graphene in DMF by weight, disperse it by ultrasonic dispersion for 1.5 hours, mix it with 40 parts of 1,6-hexanediol diglycidyl ether, add 0.1 parts of zinc formate, heat it to 40 ° C, stir the reaction for 4 hours, and centrifuge to separate the precipitate to obtain epoxy-modified graphene;

[0069] S25. By weight, 25 parts of bisphenol A epoxy resin, 4 parts of epoxy-modified graphene, 35 parts of organic solvent, 0.8 parts of defoamer were mixed, stirred and mixed for 30 minutes, vacuum defoamed, 4 parts of dicyandiamide curing agent were added, and mixing was continued for 2 minutes to obtain a heat dissipation coating;

[0070] S3. Spray the obtained heat dissipation coating on the surface of the aluminum substrate, heat it to 85-95°C, dry it for 8-20 minutes, and form a heat dissipation coating with a dry film thickness of 20 microns on the surface of the aluminum substrate to obtain an aluminum-based heat dissipation plate for energy storage batteries.

[0071] Comparative Example 1. A process for preparing an aluminum-based heat sink for an energy storage battery, comprising the following steps:

[0072] Compared with Example 1, this comparative example did not prepare epoxy-modified graphene;

[0073] S1. After polishing the surface of the aluminum substrate to remove the oxide layer, the surface is cleaned with anhydrous ethanol and acetone, dried, and set aside;

[0074] S2. Preparation of heat dissipation coating;

[0075] By weight, 25 parts of bisphenol A epoxy resin, 35 parts of organic solvent, and 0.8 parts of defoamer were mixed, stirred and mixed for 30 minutes, vacuum defoamed, 4 parts of dicyandiamide curing agent were added, and mixing was continued for 2 minutes to obtain a heat dissipation coating;

[0076] S3. Spray the obtained heat dissipation coating on the surface of the aluminum substrate, heat it to 85-95°C, dry it for 8-20 minutes, and form a heat dissipation coating with a dry film thickness of 20 microns on the surface of the aluminum substrate to obtain an aluminum-based heat dissipation plate for energy storage batteries.

[0077] Comparative Example 2. A process for preparing an aluminum-based heat sink for an energy storage battery, comprising the following steps:

[0078] Compared with Example 1, polyethylene glycol 200 was not used in step S23 of this comparative example;

[0079] S1. After polishing the surface of the aluminum substrate to remove the oxide layer, the surface is cleaned with anhydrous ethanol and acetone, dried, and set aside;

[0080] S2. Preparation of heat dissipation coating;

[0081] S21. By weight, 0.5 parts of graphene were placed in a closed chamber, and after evacuation, oxygen was filled therein to a pressure of 20Pa, and the graphene was subjected to plasma treatment, the plasma discharge power was 150W, the treatment time was 6min, and after the treatment, activated graphene was obtained;

[0082] S22. Disperse 0.5 parts of activated graphene in anhydrous ethanol by weight, ultrasonically disperse for 2-4 hours, add 25 parts of KH-550 silane coupling agent and 15 parts of deionized water, heat to 55 ° C, stir and react for 6 hours, filter and collect the precipitate, wash with anhydrous ethanol, dry and disperse it again in 50 parts of 1,1,3,3-tetramethyl-1,3-bis[3-(oxiranylmethoxy)propyl]disiloxane, heat to 80 ° C, add 0.5 parts of triethanolamine, continue ultrasonic vibration reaction for 6 hours, centrifuge and separate the precipitate, wash the precipitate with ether, and dry to constant weight to obtain the initial epoxy-modified graphene;

[0083] S23. By weight, 0.5 parts of the primary epoxy-modified graphene were added to 6.5 parts of a DMF solution of p-phenylene diisocyanate and dibutyltin dilaurate, the system temperature was controlled to 36-38 ° C, ultrasonically shaken for 5 hours, centrifuged and precipitated, and vacuum dried to constant weight to obtain hydrophilic modified graphene;

[0084] S24. Disperse 0.5 parts of hydrophilic modified graphene in DMF by weight, disperse it by ultrasonic dispersion for 1.5 hours, mix it with 40 parts of 1,6-hexanediol diglycidyl ether, add 0.1 parts of zinc formate, heat it to 40 ° C, stir the reaction for 4 hours, and centrifuge to separate the precipitate to obtain epoxy-modified graphene;

[0085] S25. By weight, 25 parts of bisphenol A epoxy resin, 4 parts of epoxy-modified graphene, 35 parts of organic solvent, 0.8 parts of defoamer were mixed, stirred and mixed for 30 minutes, vacuum defoamed, 4 parts of dicyandiamide curing agent were added, and mixing was continued for 2 minutes to obtain a heat dissipation coating;

[0086] S3. Spray the obtained heat dissipation coating on the surface of the aluminum substrate, heat it to 85-95°C, dry it for 8-20 minutes, and form a heat dissipation coating with a dry film thickness of 20 microns on the surface of the aluminum substrate to obtain an aluminum-based heat dissipation plate for energy storage batteries.

[0087] Comparative Example 3. A process for preparing an aluminum-based heat sink for an energy storage battery, comprising the following steps:

[0088] Compared with Example 1, this comparative example uses nano-silicon dioxide instead of graphene;

[0089] S1. After polishing the surface of the aluminum substrate to remove the oxide layer, the surface is cleaned with anhydrous ethanol and acetone, dried, and set aside;

[0090] S2. Preparation of heat dissipation coating;

[0091] S21. By weight, 0.5 parts of nano-silicon dioxide were placed in a closed chamber, which was filled with oxygen to a pressure of 20Pa after evacuation, and the nano-silicon dioxide was plasma treated at a plasma discharge power of 150W for 6min. After the treatment, the activated nano-silicon dioxide was obtained;

[0092] S22. Disperse 0.5 parts of activated nano-silica in anhydrous ethanol by weight, and after ultrasonic dispersion for 2-4 hours, add 25 parts of KH-550 silane coupling agent and 15 parts of deionized water, heat to 55°C, stir and react for 6 hours, collect the precipitate by filtration, wash with anhydrous ethanol, dry and disperse it again in 50 parts of 1,1,3,3-tetramethyl-1,3-bis[3-(oxiranylmethoxy)propyl]disiloxane, heat to 80°C, add 0.5 parts of triethanolamine, continue ultrasonic vibration reaction for 6 hours, centrifuge and separate the precipitate, wash the precipitate with ether, and dry to constant weight to obtain the primary epoxy-modified nano-silica;

[0093] S23. According to the weight percentage, 10 parts of polyethylene glycol 200 were dispersed in DMF, stirred evenly, and then added dropwise to a DMF solution containing 6.5 parts of p-phenylene diisocyanate and dibutyltin dilaurate under nitrogen atmosphere. The addition time was 2.5 hours. During the addition, the system temperature was controlled to be 36-38 ° C. After the addition was completed, the reaction was continued with stirring for 1.5 hours, and then 0.5 parts of the primary epoxy-modified nano-silica was added thereto. After the ultrasonic oscillation reaction was continued for 5 hours, the precipitate was separated by centrifugation, and vacuum dried to constant weight to obtain hydrophilic modified nano-silica;

[0094] S24. By weight, 0.5 parts of hydrophilic modified nano-silica were dispersed in DMF, ultrasonically dispersed for 1.5 hours, mixed with 40 parts of 1,6-hexanediol diglycidyl ether, added with 0.1 parts of zinc formate, heated to 40 ° C, stirred for 4 hours, and centrifuged to obtain epoxy-modified nano-silica;

[0095] S25. By weight, 25 parts of bisphenol A epoxy resin, 4 parts of epoxy-modified nano-silica, 35 parts of organic solvent, 0.8 parts of defoamer were mixed, stirred and mixed for 30 minutes, vacuum defoamed, 4 parts of dicyandiamide curing agent were added, and mixing was continued for 2 minutes to obtain a heat dissipation coating;

[0096] S3. Spray the obtained heat dissipation coating on the surface of the aluminum substrate, heat it to 85-95°C, dry it for 8-20 minutes, and form a heat dissipation coating with a dry film thickness of 20 microns on the surface of the aluminum substrate to obtain an aluminum-based heat dissipation plate for energy storage batteries.

[0097] Testing: The coating adhesion test was performed on the heat sinks prepared in Examples 1-4 and Comparative Examples 1-3 using the cross-hatch method according to GB / T 9286-1998; during the test, 10×10 grids of 1×1 mm were scratched on the surface of the test sample using a blade, and a tape with an adhesion of 10 N / 25 mm was used to test the scratched area. After the tape was pulled off in the reverse direction, the coating shedding was checked;

[0098] The heat sinks prepared in Examples 1-4 and Comparative Examples 1-3 were placed in a 30°C environment for 30 minutes and an 80°C environment for 30 minutes, respectively. After the cycle was repeated for 7 days, the coating adhesion test of the heat sinks prepared in Examples 1-4 and Comparative Examples 1-3 was performed again according to GB / T9286-1998;

[0099] According to GB / T 2423.17-2008, in an environment of 35°C and 90% relative humidity, 5wt% sodium chloride solution was continuously sprayed on the surface of the heat sink prepared in Examples 1-4 and Comparative Examples 1-3, and the product appearance was checked after 48 hours.

[0100] The heat dissipation plates prepared in Examples 1-4 and Comparative Examples 1-3 were cut into 50×90 cm heat dissipation plates, placed in an oven at a constant temperature of 60° C. for 30 min, and then taken out to test the surface temperature change;

[0101] The hydrophilicity test of the heat sinks prepared in Examples 1-4 and Comparative Examples 1-3 was performed using a water drop contact angle meter. The test results are shown in the following table;

[0102]

[0103] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A process for preparing an aluminum-based heat sink for an energy storage battery, characterized in that: The following steps are involved: S1. After polishing the surface of the aluminum substrate to remove the oxide layer, the surface is cleaned with anhydrous ethanol and acetone, and then dried for later use; S2. Preparation of heat dissipation coating; Mix bisphenol A epoxy resin, epoxy-modified graphene, organic solvent and defoamer, stir and mix for 30-45 minutes, remove bubbles in vacuum, add curing agent, and continue mixing for 2-4 minutes to obtain heat dissipation coating; S3. Spray the obtained heat dissipation coating onto the surface of the aluminum substrate, heat it to 85-95°C, and dry it for 8-20 minutes to obtain an aluminum-based heat dissipation plate for energy storage batteries.

2. The process for preparing an aluminum-based heat sink for an energy storage battery according to claim 1, characterized in that: In step S2, the preparation method of the epoxy-modified graphene is: S21. placing graphene in a closed chamber, evacuating the chamber and filling it with oxygen until the pressure is 15-50 Pa, subjecting the graphene to plasma treatment, and obtaining activated graphene after the treatment; S22. The activated graphene is dispersed in anhydrous ethanol, and after ultrasonic dispersion for 2-4 hours, KH-550 silane coupling agent and deionized water are added thereto, the temperature is raised to 55-65°C, and the reaction is stirred for 4-8 hours. The precipitate is collected by filtration, washed with anhydrous ethanol, and then dried and dispersed again in 1,1,3,3-tetramethyl-1,3-bis[3-(oxiranylmethoxy)propyl]disiloxane, the temperature is raised to 75-85°C, triethanolamine is added, and the ultrasonic oscillation reaction is continued for 1-8 hours. The precipitate is separated by centrifugation, washed with ether, and dried to constant weight to obtain the primary epoxy-modified graphene; S23. Disperse polyethylene glycol 200 in DMF, stir evenly, and add it dropwise to a DMF solution containing p-phenylene diisocyanate and dibutyltin dilaurate under nitrogen atmosphere for 1-4 hours. During the addition, the system temperature is controlled to be 34-40°C. After the addition is completed, continue to stir and react for 1-2 hours, add the initial epoxy-modified graphene, continue to react by ultrasonic oscillation for 2-8 hours, centrifuge and precipitate, and vacuum dry to constant weight to obtain hydrophilic modified graphene; S24. The hydrophilic modified graphene is dispersed in DMF, and after ultrasonic dispersion for 1-1.5 hours, it is mixed with 1,6-hexanediol diglycidyl ether, and zinc formate is added. The temperature is raised to 35-45°C, and the reaction is stirred for 2-6 hours. The precipitation is separated by centrifugation to obtain epoxy-modified graphene.

3. The process for preparing an aluminum-based heat sink for an energy storage battery according to claim 2, characterized in that: In step S21, during the plasma treatment, the discharge power is 150-300 W and the treatment time is 5-8 min.

4. The process for preparing an aluminum-based heat sink for an energy storage battery according to claim 2, characterized in that: In step S22, the mass ratio of the activated graphene, KH-550 silane coupling agent, and deionized water is (0.5-1.5): (25-50): (15-25).

5. The process for preparing an aluminum-based heat sink for an energy storage battery according to claim 2, characterized in that: In step S22, the mass ratio of the activated graphene, 1,1,3,3-tetramethyl-1,3-bis[3-(oxiranylmethoxy)propyl]disiloxane, and triethanolamine is (0.5-1.5):50:(0.1-0.9).

6. The process for preparing an aluminum-based heat sink for an energy storage battery according to claim 2, characterized in that: In step S23, the mass ratio of polyethylene glycol 200, p-phenylene diisocyanate, and dibutyltin dilaurate is 10:(6.5-8.1):(0.08-0.12).

7. The process for preparing an aluminum-based heat sink for an energy storage battery according to claim 2, characterized in that: In step S23, the mass ratio of the polyethylene glycol 200 to the primary epoxy-modified graphene is 10:(0.5-1.5).

8. The process for preparing an aluminum-based heat sink for an energy storage battery according to claim 2, characterized in that: In step S24, the mass ratio of hydrophilic modified graphene, 1,6-hexanediol diglycidyl ether, and zinc formate is (0.5-1.5): 40:(0.07-0.1)。 9. The process for preparing an aluminum-based heat sink for an energy storage battery according to claim 1, characterized in that: In step S2, the heat dissipation coating is composed of 20-30 parts of bisphenol A epoxy resin, 4-8 parts of epoxy-modified graphene, 30-40 parts of organic solvent, 0.5-1 part of defoaming agent, and 3-7 parts of curing agent in parts by weight; The organic solvent is a mixed solvent of xylene and butanol in a mass ratio of 2:3; The defoaming agent is an organosilicon defoaming agent; and the curing agent is dicyandiamide.

10. An aluminum-based heat sink for energy storage batteries prepared by the preparation process according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Heat dissipation plate with graphene coating

    CN103465539A

  • Siloxane and isocyanate crosslinking-modified graphene heat-conducting packing particle and preparation method thereof

    CN107033325A

  • Method for manufacturing graphene superconducting aluminum substrate

    CN108749251A

  • Isocyanate modified graphene containing heat-dissipating coating material and preparation method

    CN109266187A

  • Modified graphene oxide co-curing water-borne epoxy resin paint and preparation method thereof

    CN110054965A

Cited By

  • Shading adhesive tape for metal support of folding screen as well as preparation method and application of shading adhesive tape

    CN121343493A

  • A light-shielding adhesive tape for a folding screen metal support and a preparation method and application thereof

    CN121343493B